Open Access Process Evaluation of Teaching Critical Thinking About Health Using the Informed Health Choices Intervention in Kenya: A Mixed Methods Study - Chesire, Faith; Kaseje, Margaret; Ssenyonga, Ronald; Simon, Lewin (Global Health: Science and Practice, 2024)
We evaluated the Informed Health Choices secondary school intervention to help students in Kenya think critically about health choices. We conducted this process evaluation to explore if the intervention was implemented as planned, identify factors that facilitated or hindered implementation, potential benefits of the intervention, and how to scale up the intervention beyond the trial This was a mixed methods process evaluation nested in a cluster-randomized trial of the Informed Health Choices intervention. We analyzed quantitative data from teacher training evaluation forms completed by 39 teachers, 10 lesson evaluation forms completed by 40 teachers allocated to the intervention, and 72 structured classroom observation forms. We conducted a framework analysis of qualitative data from 14 group interviews (with 96 students, 23 teachers, and 18 parents) and 22 individual interviews (with 8 teachers, 5 school principals, 6 curriculum developers, and 3 policymakers). We assessed confidence in our findings from the qualitative analysis using a modified version of Confidence in the Evidence from Reviews of Qualitative Research. Lesson objectives were achieved with minimal adaptations. Factors that might have facilitated the implementation of the intervention include teacher training; perceived value of the intervention by students, teachers, and policymakers; and support from school administration. Time constraints, teachers’ heavy workloads, and the lessons not being included in the curriculum or national examination are factors that might have impeded implementation. Both students and teachers demonstrated the ability to apply key concepts that were taught to health choices and other choices. However, they experienced difficulties with 2 of the lessons. Scale-up of this intervention in Kenyan schools is feasible but may depend on adjusting the time allocated to teaching the lessons, modifying the 2 lessons that teachers and students found difficult, and including the lesson objectives and assessment in the national curriculum.